ETHNOMEDICINAL STUDIES IN SELECTED MEDICINAL PLANTS OF DHONI FOREST, WESTERN GHATS, KERALA. - JAYA PRIYA.V.K; Gopalan, R. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The objective of the study was to identify and utilize medicinal plants used by Irula tribal’s of Dhoni Forest, Kerala. Methods: Frequent field visits were made throughout the study period from October 2011 to June 2012 in the study area. Results: A total of 32 medicinal plant species used by the Irula tribes were documented. These medicinal plant species were distributed in 23 families and 32 genera. In terms of number of medicinal plant species, Apocynaceae, Malvaceae and Menispermaceae were the most dominant families of medicinal plants. The results of the present study provide evidences that medicinal plants continue to play an important role in the health care system of the tribal community. Conclusion: The treasure of knowledge on traditional medicine is gradually vanishing due to modernization and civilization of tribal community and also the younger generation not showing any interest in learning those practices. The collected detailed information on the list of plants and their therapeutic practices among Irula tribes may be helpful to improve the future pharmaceutical applications. Â Key words: Dhoni Forest, Irula tribe, medicinal plants, Ethnomedicinal uses.